2015
DOI: 10.1242/dev.123950
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptional symmetry-breaking in pre-implantation mammalian embryo development revealed by single-cell RNA-seq

Abstract: During mammalian pre-implantation embryo development, when the first asymmetry emerges and how it develops to direct distinct cell fates remain longstanding questions. Here, by analyzing single-blastomere transcriptome data from mouse and human preimplantation embryos, we revealed that the initial blastomere-toblastomere biases emerge as early as the first embryonic cleavage division, following a binomial distribution pattern. The subsequent zygotic transcriptional activation further elevated overall blastomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 53 publications
3
100
0
Order By: Relevance
“…In agreement, single-cell transcriptomic analyses of mouse embryos show that at least one blastomere in a four-to eightcell stage embryo exhibits low levels of expression of a gene downstream of Sox2 (Goolam et al, 2016), suggesting that cell lineage determination occurs much earlier than morphologically observed. These observations also reinforce the notion that cell division partitioning errors (Shi et al, 2015) or random transcriptional noise (Eldar and Elowitz, 2010;Elowitz et al, 2002) could be the mechanism that drives symmetry breaking in the embryo. In summary, several common mechanisms emerge from the analysis of symmetry breaking both in vivo and from reconstituted systems.…”
Section: Breaking Symmetrysupporting
confidence: 78%
“…In agreement, single-cell transcriptomic analyses of mouse embryos show that at least one blastomere in a four-to eightcell stage embryo exhibits low levels of expression of a gene downstream of Sox2 (Goolam et al, 2016), suggesting that cell lineage determination occurs much earlier than morphologically observed. These observations also reinforce the notion that cell division partitioning errors (Shi et al, 2015) or random transcriptional noise (Eldar and Elowitz, 2010;Elowitz et al, 2002) could be the mechanism that drives symmetry breaking in the embryo. In summary, several common mechanisms emerge from the analysis of symmetry breaking both in vivo and from reconstituted systems.…”
Section: Breaking Symmetrysupporting
confidence: 78%
“…Recent single-cell transcriptomic studies have also highlighted the presence of heterogeneities in gene expression in early blastomeres (Biase et al, 2014;Deng et al, 2014;Piras et al, 2014;Shi et al, 2015). Gene expression heterogeneity is observed as early as the 2-cell stage.…”
Section: Introductionmentioning
confidence: 99%
“…one has high expression, the other has low), some bimodally expressed genes show correlation or anti-correlation with other genes, suggesting that the heterogeneity is not due to random transcriptional noise. For example, most blastomeres in 8-cell embryos are dominated either by Carm1 or by Cdx2 (Shi et al, 2015). Whether this heterogeneity is sufficient to control subsequent cellular behaviour needs to be tested in the future.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the focus of single-cell studies in the mouse embryo has been on gene expression patterns that characterize particular developmental stages or lineages within the blastocyst or mono versus bi-allelic gene expression (Biase et al, 2014;Deng et al, 2014;Guo et al, 2010;Shi et al, 2015;Tang et al, 2011;Xue et al, 2013), rather than on investigating the functional consequences of heterogeneity within the same embryo for cellfate specification. Here, using single-cell transcriptomics, we determined the extent of transcriptional heterogeneities between individual cells in pre-implantation embryos and identified that target genes of the pluripotency master regulators Oct4 and Sox2 are highly heterogeneous at the 4-cell stage.…”
Section: Introductionmentioning
confidence: 99%